Practices, Challenges and Lessons Learned in Selected Lodging Accommodations in Zambales: Basis for Sustainable Operations - Michelle Van M. Eusebio-Sison; Rovena I. Dellova (Inclusive Society and Sustainability Studies, 2023)
Adopting sustainability strategies improves a company's efficiency on many levels, including quality of work, a good track record, image improvement, and major investor commitment that affects its operations. This descriptive study aimed to explore the critical viewpoint of the current challenges and lessons learned in selected lodging accommodations in Zambales, Philippines. It employed a sequential explanatory mixed-methods design using purposive sampling with 400 respondents. The Kruskal-Wallis test revealed that there is a significant difference in the perception of the respondents when they are grouped according to job positions. Resort and hotel workforces must be qualified in accordance with their positions, and continuous training is important to inculcate a sense of responsibility. Also, there is a little causal relationship between practices in socio-cultural, economic, and environmental aspects. Employees are not mindful of their practices as to whether they are attributable to sustainable operations. It also reveals that 379 out of 400 resorts and hotels have an existing plan that they are seriously crafting and implementing to address the challenges of their operations. They undertake appropriate measures to ensure that management is responsive to the impacts of tourism. Thus, long-term solutions are stressed to promote the environmental, economic, and social management plans for guest satisfaction and effective overall performance for sustainable lodging accommodations in the region.